Anal canal neuroendocrine tumour:: a rare case report - S L, Liew; Sainal, Mohd. Yusof; Elagili, Faisal; Md Nor, Azmi (2022)
INTRODUCTION Neuroendocrine tumours of the anal canal are extremely uncommon, with only a few cases previously reported in the medical literature. OBJECTIVE We present a case of neuroendocrine tumour of the anal canal. CASE REPORT A 42-year-old man with no known medical conditions presented with left iliac fossa pain that had persisted for two weeks. The physical exam was unremarkable. Colonoscopy revealed a small whitish round tumour 9 mm in diameter just above the dentate line, as well as diverticular lesions in the descending, transverse, and ascending colon. The biopsy results are consistent with a well-differentiated neuroendocrine tumour. Under sedation, endoscopic mucosal resection was performed, and the HPE revealed a low-grade NET with a Ki-67 proliferative index of less than 2% and a margin clear but 1mm away. We planned on having a surveillance colonoscopy in a year. CONCLUSION Anal canal neuroendocrine carcinomas are extremely rare tumours, with only a few cases previously reported. Because no proper guidelines have been established, our case was treated in accordance with the colorectal NET guideline. More cases, however, are needed to identify prognostic factors, validate treatment modalities, and determine the best management strategy.